Construction of hybrid Muslim identity in Zohran Mamdani's political communication: A critical discourse analysis - Shintadewi, Luthfina Cahyani; Ubaidillah, Ubaidillah (University of Muhammadiyah Malang, 2026)
This study examines the construction of Muslim identity in Zohran Mamdani's political communication in the United States by analyzing how lexical choices shape meaning in multicultural political spaces. Previous studies show that Islamophobia and post-9/11 narratives continue to marginalize Muslim identities, yet little attention is given to how Muslim political figures construct their identities through political communication, highlighting the urgency of this study. The purpose of this research is to explain how lexical choice and narrative structures are used to frame Muslim identity as an equal and legitimate entity. This study uses a qualitative approach, utilizing Fairclough's Critical Discourse Analysis to understand identity negotiations in political communication discourse, with the concept of hybrid identity as its basis. The methodology involves a three-dimensional analysis: textual level, discursive practices, and social practices. The dataset consisted of five public communication materials including victory speeches, media interviews, and podcast appearances. The findings show that Zohran Mamdani constructs a hybrid Muslim identity through strategic use of linguistic features which reposition Muslims as active moral and political agents. His discourse adapts across communication platforms while maintaining ideological consistency, and actively engages with broader socio-political issues such as Islamophobia, minority representation, and national belonging. These findings contribute to the broader field of critical discourse studies by demonstrating how linguistic strategies are used to negotiate identity, power, and social positioning. This study also offers practical implications for political communication, suggesting that inclusive and strategically constructed discourse can challenge Islamophobic narratives and foster more equitable representation of minority groups.